2014
DOI: 10.2495/cr140601
|View full text |Cite
|
Sign up to set email alerts
|

Towards a simulation-based framework for evaluating energy-efficient solutions in train operation

Abstract: In this paper we propose a simulation-based framework for evaluating energyefficient solutions in train operation. The general framework is composed of an optimisation system able to generate energy-efficient station-to-station speed profiles, looped with a micro-simulation tool for simulating railway traffic conditions, in order to evaluate the impacts on railway systems (delays, conflicts) and energy savings. The optimisation system is a subroutine consisting of a Genetic Algorithm for optimal speed profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In [29], the potential effects of energy-efficient driving profiles on consumption were studied with a parametric approach in an Italian region; the results showed that up to 20% of total traction energy can be saved by optimising speed profiles and up to 35% if trains are equipped with braking energy recovery systems. Simulation-based methods can be found in [30][31][32][33].…”
Section: Railway Energy-efficient Drivingmentioning
confidence: 99%
“…In [29], the potential effects of energy-efficient driving profiles on consumption were studied with a parametric approach in an Italian region; the results showed that up to 20% of total traction energy can be saved by optimising speed profiles and up to 35% if trains are equipped with braking energy recovery systems. Simulation-based methods can be found in [30][31][32][33].…”
Section: Railway Energy-efficient Drivingmentioning
confidence: 99%
“…In recent years, research has been very focused on ecodriving applied to rail transport [78][79][80][81][82][83][84][85][86][87][88][89]. Although the rail transport system is more environmentally friendly, energy consumption and greenhouse gas emissions, where the energy consumed is not produced from renewable sources, are still high.…”
Section: Ecodrivingmentioning
confidence: 99%
“…As regard to the adopted methodological approaches, the most common methods for analyzing these strategies are based on integrated simulation-optimization techniques, both in off-line [52,53] and real-time [54][55][56][57][58][59][60][61] contexts. On the other hand, analytical approaches for modelling the implementation of ES strategies can be found in [4,[62][63][64].…”
Section: Literature Reviewmentioning
confidence: 99%